2015
DOI: 10.1016/j.addr.2014.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Virus integration and genome influence in approaches to stem cell based therapy for andro-urology

Abstract: Despite the potential of stem cells in cell-based therapy, major limitations such as cell retention, ingrowth, and trans-differentiation after implantation remain. One technique for genetic modification of cells for tissue repair is the introduction of specific genes using molecular biology techniques, such as virus integration, to provide a gene that adds new functions to enhance cellular function, and to secrete trophic factors for recruiting resident cells to participate in tissue repair. Stem cells can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 88 publications
0
6
0
Order By: Relevance
“… 64 , 65 The enhancement of cellular retention, cellular differentiation, and cellular paracrine effects after transplantation are the mechanisms by which the abovementioned engineered stem cells exert powerful effects. 66 The research and application of novel biomaterials have brought new opportunities for the development of SCT in ED. The retention time of stem cells in the corpus cavernosum is extended when combined with materials such as hydrogels, scaffolds, and magnetic nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“… 64 , 65 The enhancement of cellular retention, cellular differentiation, and cellular paracrine effects after transplantation are the mechanisms by which the abovementioned engineered stem cells exert powerful effects. 66 The research and application of novel biomaterials have brought new opportunities for the development of SCT in ED. The retention time of stem cells in the corpus cavernosum is extended when combined with materials such as hydrogels, scaffolds, and magnetic nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…It is showed that combing cell therapy with gene therapy remarkably improve differentiation of implanted MSCs, revascularization, and innervation in genitourinary tissues, especially in the treatment of ED. [24] Bivalacqua. et al [11] rst used the genetic BM-MSCs modi cation technique on treating ED, which using MSCs modi ed with endothelial nitric oxide synthase (eNOS) to reverse age-associated ED.…”
Section: Discussionmentioning
confidence: 99%
“…13,20 These genetically engineered MSCs can thereby both improve MSC engraftment and functionality, while also allowing for the targeted delivery of therapeutic gene products that can enhance local tissue healing. 21 Indeed, MSCs can secret a broad profile of active molecules including hematopoietic growth factors, angiogenic growth factors, trophic molecules, immunomodulatory cytokines, and chemokines. The best-characterized GFs and cytokines produced by these cells are compiled in Table 1.…”
Section: The Relationship Between Msc Biology and Gf Secretionmentioning
confidence: 99%